Environmental sustainability practices among palm oil millers - Begum, Halima; Alam, A. S. A. Ferdous; Er, A. C.; Abdul Ghani, Ahmad Bashawir (Springer Nature Switzerland AG, 2019)
Considering the global palm oil production, it can be identified as the second largest vegetable oil. Palm oil is a natural resource that is favorable for the Malaysian climate. In 2017, Malaysia had a total of 454 palm oil mills with a production capacity of approximately 112 million tonnes of fresh fruit bunches. A sustainable environment denotes high income, value addition and zero waste. Nonetheless, palm oil mills are being associated with the discharge of untreated effluent water stream pollution, solid wastes, air pollution, etc. The important objective of this study is to measure the level of sustainable environmental practices parameters and awareness of millers. The primary data were collected through questionnaire survey and interviews from 71 millers in Malaysia. This study used confirmatory factor analysis to describe the relationships between the environmental parameters for measuring environment sustainability. This study found that most of the millers employ positive practices for environmental sustainability, and the highest environment parameter is disposal of solid wastes. However, this study can be implemented in Malaysian palm oil mills for identifying the lowest parameters. This study suggested to the industries that the new national sustainable policies for palm oil mills, especially for small and medium players, may enhance the environmental parameters.